Comparative evaluation of clinical and radiographic success of three different lesion sterilization and tissue repair techniques as treatment options in primary molars requiring pulpectomy: An in vivo study - Amolkumar Lokade; Seema Thakur; Parul Singhal; Deepak Chauhan; Chiranjeevi Jayam (Wolters Kluwer Medknow Publications, 2019)
Introduction: Paediatric endodontics is part of paediatric dental practice. Teeth with infected root canals, particularly those in which the infection has spread around the apical foramen and furcation area, is a common problem in primary dentition for such conditions pulpectomy is the procedure. Pulpectomy procedure proves to be long and complicated and has remained controversial for a number of reasons. Lesion sterilization and tissue repair therapy (LSTR) is a relatively new biologic approach for carious lesions with or without pulpal and periapical involvement using a mixture of antibiotics. Objectives: The aim of this study was to evaluate clinical and radiographic success of three different LSTR techniques as treatment options in primary molars requiring pulpectomy. Methods: Sixty-three primary molars of fifty children aged between 4 and 8 years with primary molars requiring pulpectomy were treated with modified 3Mix-MP antibiotic paste without removal of accessible radicular pulp (Group I), modified 3Mix-MP with removal of accessible radicular pulp (Group II) and Chloramphenicol, tetracycline and zinc oxide eugeno (CTZ) paste (Group III). The subjects were followed up clinically at one, six, and twelve months whereas radiographically at six and twelve months, respectively. Results: The results showed that clinical success rates of Group I, Group II and Group III were 90%, 90.5% and 81.8% respectively and radiographical success rates were 75%, 76.2% and 63.6% respectively after twelve months observation. Conclusion: On the basis of the overall success rates of all the three LSTR techniques, following order of performance can be inferred clinical success and radiographical success: - 3Mix-MP without removal of radicular pulp = 3Mix-MP with removal of radicular pulp >CTZ paste.